Observational Evidence and Open Questions on the Role of Internal Tidal Waves on the Concentration and Transport of Floating Plastic Debris - Alan L. Shanks (Frontiers in Marine Science, 2021)
Tidal currents flowing over benthic relief (e.g., banks, shelf break) can produce large internal waves. These waves propagate away from their origin and are capable of crossing the continental shelf and seas. Studies of shoreward transport of larval invertebrates and fish by these internal waves unintentionally tested whether they can capture, concentrate and transport floating plastic. Plastic surface drifters deployed in front of sets of internal wave convergences were often captured (>90% captured) and transported kilometers by the waves. There are, however, few investigations into how internal tidal waves may affect the fate and distribution of floating plastic waste. A number of areas of future research are suggested: (1) How much floating plastic is found in internal wave convergences? (2) How buoyant must floating plastic be to be captured by internal waves? (3) Why did only some sets of internal waves cause concentration and transport of surface material? (4) Do concentration and transport of floating plastic vary over the spring/neap tidal cycle? (5) Do seasonal changes in the depth of the pycnocline alter the transport of floating plastic by internal waves? (6) Plastic debris deposited on shore may not be evenly distributed, but may be more abundant landward of sites on the shelf break that more readily generate large internal waves. (7) Internal waves that travel long distances (10–100 s of km) have the potential to accumulate large amounts of plastic debris. (8) At locations where internal waves cross the continental shelf, how far offshore does transport commence?